First-principles calculations to investigate the effect of Cs-doping in BaTiO3 for water-splitting application. (1st November 2022) - Usman, Muhammad; Rehman, Jalil Ur; Tahir, M. Bilal; Hussain, Abid
Abstract: The structural, electronic, and optical properties of the pure and Cs-doped BaTiO3 are investigated theoretically with the help of Cambridge Serial Total Energy Package code, which utilizes an ultra-soft pseudopotential plane wave and a Perdew Burke Ernzerhof exchange-correlation functional of the Generalized Gradient Approximation. The DFT + U approximation is employed to get the better results for electronic properties. The calculated lattice parameters and bandgap for pure BaTiO3 are found 4.034 Å and 2.513 eV which are consistent with the previous studies. The pure BaTiO3 possesses an indirect while the Cs-doped BaTiO3 systems have a direct band gap. The value of band gap is found 1.858, 2.103 and 1.882 eV for 0.13, 0.26 and 0.39% Cs-doped BaTiO3, respectively. For pure BaTiO3, the absorption edge is in the invisible region, whereas, the Cs-doped (0.13%) BaTiO3 possesses the maximum absorption edge in the visible region. By introducing the new Cs-3p states into the valence band of BaTiO3, the photocatalytic activity of the material is enhanced. For 0.26 and 0.39% Cs-doped BaTiO3, the absorption edge in the visible region is found lower than that of 0.13% Cs-doped BaTiO3 . Moreover, 0.13% Cs-doped BaTiO3 possesses a minimal energy loss than that of 0.26 and 0.39% Cs-doped BaTiO3 . Therefore, 0.13% Cs-doped BaTiO3 is found an efficient candidate for photocatalytic water-splitting by studying the combined effect of electronic and optical properties. Highlights: The structural, electronic and optical properties of pure and Cs-doped BaTiO3 are investigated by using DFT + U approach. The pure BaTiO3 has an indirect band gap and possesses the absorption edge in the invisible region which is not suitable to perform the photocatalytic water-splitting. The combined effect of electronic and optical properties suggests that 0.13% Cs-doped BaTiO3 is an efficient candidate for photocatalytic water-splitting.